Establishment of an Acute Karoshi Rat Model and Its Metabolic， Functional and Morphological Changes - LIU Xia; LI Jia-min; ZHENG Yong-xia; XIAO Xu-dong; YU Xiao-jun (Fayixue Zazhi, 2024)
ObjectiveTo investigate the occurrence and mechanism of acute Karoshi and explore its forensic identification.MethodsSD rats were divided into the control group （n=15） and experimental groups （n=45, acute Karoshi group and overwork survival group）. A severe fatigue model was established by combining forced swimming under load to exhaustion and sleep deprivation. Their daily activities, diets, weight, respiratory functions, electrocardiogram and echocardiography were recorded. After the rats were sacrificed, samples were collected at autopsies. HE staining was used to observe the pathological morphology, and GC-MS was used to detect the changes of substance metabolism in serum, myocardium and liver.ResultsThe mortality rate of the experimental group was 33.3%. There were decreases of aminobutyric acid and arachidonic acid in myocardium tissues, decreases of urea and increases of methionine and phenylalanine in serum. In liver tissues, the content of amino acids sush as histidine increased. The blood biochemical testing showed increases of alanine aminotransferase, aspartate aminotransferase, creatine kinase and creatine kinase isoenzymes and decreases of glucose and uric acid. There were interferences of energy metabolism pathways in serum, heart, and liver tissues. After three days, the experimental group developed cardiac conduction block and ventricular arrhythmia. Ventricular fibrillation and ventricular flutter appeared in acute Karoshi group. Echocardiogram showed ejection fraction and left ventricular short axis shortening rate decreased. The histological examination showed granular swelling and sarcoplasmic condensation in myocardium and increased dark neurons in the brain stem. The combination of differential metabolites of serum urea, methionine and phenylalanine was highly correlated with Karoshi with a diagnostic rate of 90.6%.ConclusionAcute Karoshi can trigger a cascade reaction of metabolic, functional and morphological changes. The mechanism of death, especially central failure and sudden cardiac death, may be associated with multi-organ failure.